Voz no teatro: efeitos de uma intervenção com foco no registro vocal - Pedra, Ariane Moulin (2016)
Introduction: voice is an essential element in the preparation of actors, and an integral part of the character creation process. To be able to involve the audience in his or her acting, an actor should have, among other requisites, total domain over his or her body and voice. Objective: to assess the effects of a speech-language intervention focused on vocal register in the spoken voice of theater actors. Method: this research involved 53 theater actors, who were submitted to an intervention focused on their vocal registers. For the gathering of speech samples, the subjects were requested to record, before and after the intervention, an excerpt of the selected theater play. Two people were invited to sit in the audience to contextualize the actors performances. The material recorded before and after the intervention was edited randomly and the order was determined via an intra-subject draw, and presented separately to a panel of three speech therapists, who then conducted an auditory perceptual assessment. The assessment instrument was elaborated through a pilot study. The data were analyzed statistically, considering the average of each parameter and the comparison between the different assessments of the two moments (before and after the intervention). Results: there was a statistically significant difference between the before and after moments for all variables, particularly in regard to loudness and voice projection, which gained 1 point. Conclusion: the proposed intervention focused on vocal register produced positive effects on the subjects voices, and may be a useful tool for speech therapists working with actors, increasing these professionals vocal well-being and improving the techniques they employ on stage